TFH Cells Induced by Vaccination and Following SIV Challenge Support Env-Specific Humoral Immunity in the Rectal-Genital Tract and Circulation of Female Rhesus Macaques - Helmold Hait, Sabrina; Hogge, Christopher James; Rahman, Mohammad Arif; Hunegnaw, Ruth; Mushtaq, Zuena; Hoang, Tanya; Robert-Guroff, Marjorie (Frontiers in Immunology, 2021)
T follicular helper (TFH) cells are pivotal in lymph node (LN) germinal center (GC) B cell affinity maturation. Circulating CXCR5+ CD4+ T (cTFH) cells have supported memory B cell activation and broadly neutralizing antibodies in HIV controllers. We investigated the contribution of LN SIV-specific TFH and cTFH cells to Env-specific humoral immunity in female rhesus macaques following a mucosal Ad5hr-SIV recombinant priming and SIV gp120 intramuscular boosting vaccine regimen and following SIV vaginal challenge. TFH and B cells were characterized by flow cytometry. B cell help was evaluated in TFH-B cell co-cultures and by real-time PCR. Vaccination induced Env-specific TFH and Env-specific memory (ESM) B cells in LNs. LN Env-specific TFH cells post-priming and GC ESM B cells post-boosting correlated with rectal Env-specific IgA titers, and GC B cells at the same timepoints correlated with vaginal Env-specific IgG titers. Vaccination expanded cTFH cell responses, including CD25+ Env-specific cTFH cells that correlated negatively with vaginal Env-specific IgG titers but positively with rectal Env-specific IgA titers. Although cTFH cells post-2nd boost positively correlated with viral-loads following SIV challenge, cTFH cells of SIV-infected and protected macaques supported maturation of circulating B cells into plasma cells and IgA release in co-culture. Additionally, cTFH cells of naïve macaques promoted upregulation of genes associated with B cell proliferation, BCR engagement, plasma cell maturation and antibody production, highlighting the role of cTFH cells in blood B cell maturation. Vaccine-induced LN TFH and GC B cells supported anti-viral mucosal immunity while cTFH cells provided B cell help in the periphery during immunization and after SIV challenge. Induction of TFH responses in blood and secondary lymphoid organs is likely desirable for protective efficacy of HIV vaccines.